3X+2X+1+6=50-3

Simple and best practice solution for 3X+2X+1+6=50-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3X+2X+1+6=50-3 equation:


Simplifying
3X + 2X + 1 + 6 = 50 + -3

Reorder the terms:
1 + 6 + 3X + 2X = 50 + -3

Combine like terms: 1 + 6 = 7
7 + 3X + 2X = 50 + -3

Combine like terms: 3X + 2X = 5X
7 + 5X = 50 + -3

Combine like terms: 50 + -3 = 47
7 + 5X = 47

Solving
7 + 5X = 47

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 5X = 47 + -7

Combine like terms: 7 + -7 = 0
0 + 5X = 47 + -7
5X = 47 + -7

Combine like terms: 47 + -7 = 40
5X = 40

Divide each side by '5'.
X = 8

Simplifying
X = 8

See similar equations:

| -2x-10=-16 | | 3x^2-27x+18=0 | | -2x-18=12+3x | | e^3x=.833333333333 | | 1.66(6x)= | | 1+4x=31 | | 2m^2+17m+22=0 | | 8c-7=5c+2 | | 4(x-y)+7= | | x-15=-3x+13 | | 6e^3x+4=9 | | 3G-22=-4-3g | | 16x^3-10x^2+14x= | | 4p^2-19p-5=0 | | 4(3e-2)=5(e+4) | | -4x+1=-47 | | 11t-13=3t-11 | | 3(4d-2)=5(3-d) | | 16-36-5= | | 28x^2-x-12=0 | | -22=x+-8 | | 6x+5=4-9 | | x+x+9+x+x+5=x+x+x+x+x | | 5(2a-6)=40 | | t-3/2=8/9 | | -25+25+4= | | 2(4x-3.1)=9x-6.2 | | t-3/3=8/9 | | -3+5x=-63 | | 6*11-8=72 | | E-6=-8 | | x^3-4x^2+4x-16= |

Equations solver categories